Malayalam Orthographic Reforms: Impact on Language and Popular Culture - Kavya Manohar and Santhosh Thottingal
Malayalam is a language spoken in India, predominantly in the state of Kerala with about 38 million native speakers. The Malayalam script evolved from Brahmi through Grantha alphabet and Vattezhuthu writing systems. The script orthography has acquired its uniqueness with its complex shaped ligatures formed by the combination of consonants and vowel sign forms. The number of unique graphemes in this system exceeds 1200. The orthographic styles were constantly evolving. In 1971 there was a Governmental intervention in the or- thography, to reduce its complexity to address the difficulties in typesetting and printing. This paper is an attempt to explore the impact of this orthographic re- forms on various aspects of script usage including popular culture, media, text- books, graffiti and handwriting. We will also analyse the impact of Unicode and the advancement in digital typography on the orthographic diversity of Malay- alam script